Effect of boiling time on chemical composition and physico-functional properties of flours from taro (Colocasia esculenta cv fouê) corm grown in Côte d’Ivoire - Amon, Anon Simplice (Springer India, 2011)
Taro (Colocasia esculenta cv fouê) corm was subjected to different boiling times and the changes in chemical composition and physico-functional properties were investigated using standard method. The change in boiling time led to a significant (P < 0.05) reduction in the moisture, reducing sugars, total sugars, crude fat, crude fibre, total phenolic compound contents and iodine affinity of starch, whereas the total carbohydrate content, water absorption capacity, water solubility index, paste clarity and foam capacity increased significantly (p < 0.05). The crude protein and total ash contents of the flours from taro corm were not affected significantly (p < 0.05) by the change in boiling time. Taro corm flours exhibited highest total carbohydrate, crude fibre, total ash contents, water absorption capacity, iodine affinity of starch and lowest crude protein and fat contents, foaming capacity and water solubility index. Principal component analysis showed that flours from taro corm boiled during 20 min and 15 min were located at the left of the score plot, while flours from raw and boiled taro corm during 10 min had a large positive score in the first principal component.